Case of Peritoneal Malignant Mesothelioma in a 60-year-old Lady Presenting Clinically With Huge Abdominopelvic Mass: A Diagnostic Challenge - Usha Sarma; Rituparna Das; Mayurpankhi Saikia (Journal of Clinical and Diagnostic Research, 2024)
Peritoneal malignant mesothelioma is a rare tumour that poses diagnostic challenges due to vague clinical symptoms, a variable histologic picture and being a common site for metastasis from GI organ, ovary, kidney and several other organs. We presented a case of peritoneal malignant mesothelioma in a 60-year-old lady who presented clinical symptoms of abdominal obstruction due to an omental cyst on a Computed Tomography (CT) scan. The case has been diagnosed as peritoneal malignant mesothelioma on histology along with a panel of immunohistochemical stains like calretinin (diffuse nuclear and cytoplasmic positivity), WT1 (diffuse nuclear positivity), CK 7 (focal positivity), PAX8 (focal positivity), CK20 (negative). At least two positive immunohistochemical markers and one negative marker help to distinguish mesothelioma from other entities. There was no history of active or passive asbestos exposure. She has been referred to a nearby regional cancer centre and managed accordingly. During her first postoperative check-up, she was asked about the history of asbestos exposure either in active or in passive form, which she denied. The present case report discusses the diagnostic dilemma in routine Haematoxylin & Eosin (H&E) stained tissue sections with a list of differential diagnoses as: 1) Primary tumour (peritoneal malignant mesothelioma versus primary serous carcinoma); 2) Sex cord-stromal tumour of ovarian origin; 3) Metastatic adenocarcinoma from neighbouring organ.